A stretchable transparent electromagnetic shielding film imitating a fence structure and a preparation method thereof

By changing the release environment in the pre-stretch-release strain method, the silver nanowire conductive network forms an orientation distribution of the fence structure, and solving the conductive stability and electromagnetic shielding performance of flexible and stretchable transparent electromagnetic shielding films in the prior art. The problem of this achieves a combination of high optical transmittance and high electromagnetic shielding performance.

CN115135128BActive Publication Date: 2025-02-14ZHENGZHOU UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210788566.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-06
Publication Date
2025-02-14
Estimated Expiration
2042-07-06

AI Technical Summary

Technical Problem

The prior art is difficult to ensure the conductive stability and electromagnetic shielding performance of flexible and stretchable transparent electromagnetic shielding films while maintaining high optical transmittance and high density AgNW overlap.

Method used

By changing the release environment in the pretension-release strain method and using water covering and blow-drying methods, the silver nanowire conductive network slowly releases the prestrain in a wet environment, thus forming a silver nanowire orientation distribution that is imitated with fence structure.

Benefits of technology

The conductive network structure without silver nanowire fracture is realized, high light transmittance and conductive stability are maintained, and electromagnetic shielding performance is ensured under large deformation conditions, with small surface resistance, high transparency and excellent electromagnetic shielding performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115135128B_ABST
    Figure CN115135128B_ABST
Patent Text Reader

Abstract

The present invention belongs to the technical field of transparent electromagnetic shielding films, and discloses a fence-like stretchable transparent electromagnetic shielding film and a preparation method thereof. It comprises an elastic transparent substrate layer and a surface layer deposited thereon, wherein the elastic transparent substrate layer is a DMS film or a TPU film, and the surface layer is an AgNW conductive network layer, and the silver nanowires are distributed in a fence-like structural orientation on the elastic transparent substrate layer. The preparation steps are as follows: surface modification treatment of the elastic transparent substrate layer is performed with O2 plasma in a vacuum environment; unidirectional pre-stretching is performed until strain occurs, and a silver nanowire dispersion is sprayed on its surface; a layer of water is evenly covered, and after soaking, residual surface water is blown off, and the pre-stretching strain is slowly released to a completely relaxed state, and annealing treatment is performed. The silver nanowire conductive network with a fence-like structural orientation formed by the present invention is beneficial to the photoelectric performance of the transparent film, while ensuring the stable conductivity and electromagnetic shielding performance of the conductive network under large deformation.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of transparent electromagnetic shielding films, and in particular relates to a stretchable transparent electromagnetic shielding film with an imitation fence structure and a preparation method thereof. Background Art

[0002] In the modern electronics industry, flexible transparent conductive film (TCF) is widely used in solar cells, touch screens, flexible displays, smart windows, electromagnetic interference shielding, etc. In particular, in the face of increasingly severe electromagnetic radiation pollution, TCF as an electromagnetic shielding material shows great application potential in specific application scenarios such as visual optical windows / displays. At present, the conductive material used in transparent conductive films widely used in industry is mainly indium tin oxide (ITO). However, its lack of flexibility, high manufacturing cost and scarce indium tin resources limit its application as a new generation of flexible and stretchable transparent conductive films in the field of transparent electromagnetic shielding.

[0003] In recent years, researchers have found that one-dimensional silver nanowires (AgNWs) with ultra-high conductivity and high aspect ratio can easily form a continuous surface conductive network, and there are abundant gaps between the AgNW conductive networks, allowing most of the light to pass through, that is, high optical transmittance. Therefore, AgNW has become one of the most ideal conductive materials for preparing flexible transparent conductive films. In view of the rigid structure of AgNW, researchers usually use the pre-stretching-strain release method to prepare stretchable transparent conductive films, that is, AgNW is deposited on the surface of a pre-stretched elastic substrate, and then when the pre-strain is released, the AgNW conductive network layer produces local slip or deformation, thereby forming an AgNW conductive network with a wrinkled or wavy structure. Lee et al. found (Adv. Funct. Mater. 2020, 30, 1910214) that due to the huge difference in modulus between the rigid AgNW and the elastic substrate, releasing the pre-strain in the air caused the AgNW to break, seriously affecting the conductive stability of the TCF obtained; at the same time, their research also found that water can effectively swell the PVP layer on the surface of AgNW and regulate the stiffness of AgNW. Releasing the pre-strain in water can obtain an in-plane wavy structure AgNW conductive network with stretchable properties.

[0004] However, whether it is the random distribution of AgNW or the formation of a wavy or wrinkled network structure, it is difficult to ensure high light transmittance when forming a high-density AgNW overlap. In comparison, the oriented distribution of AgNW is believed to be able to build an efficient conductive network while ensuring high light transmittance. Therefore, in the face of the urgent need for a new generation of flexible, stretchable, transparent electromagnetic shielding films, it is urgent to develop a transparent electromagnetic shielding film that is both stretchable, highly transparent, and oriented with AgNW. Summary of the invention

[0005] In order to solve the deficiencies in the prior art, the object of the present invention is to provide a stretchable transparent electromagnetic shielding film with an imitation fence structure and a preparation method thereof.

[0006] To achieve the above purpose, the technical solution adopted by the present invention is as follows:

[0007] A fence-like stretchable transparent electromagnetic shielding film comprises an elastic transparent base layer and a surface layer deposited thereon, wherein the elastic transparent base layer is a polydimethylsiloxane (PDMS) film or a thermoplastic polyurethane (TPU) film, and the surface layer is a silver nanowire (AgNW) conductive network layer, and the silver nanowires are distributed on the elastic transparent base layer in a fence-like structure orientation.

[0008] A method for preparing a stretchable transparent electromagnetic shielding film with a fence-like structure, the preparation steps are as follows:

[0009] (1) Using O2 plasma to perform surface modification on the elastic transparent substrate in a vacuum environment;

[0010] (2) uniaxially pre-stretching the elastic transparent substrate layer subjected to surface modification treatment in step (1) (usually in the length direction or width direction, but not in the thickness direction) until strain occurs, and spraying a silver nanowire dispersion on the surface of the elastic transparent substrate layer to form a silver nanowire transparent conductive network;

[0011] (3) The surface of the silver nanowire conductive network formed in step (2) is uniformly covered with a layer of water. After soaking, the residual water on the surface is blown away, and the pre-stretching strain is slowly released to a completely relaxed state, and annealing is performed to obtain a fence-like structure stretchable transparent electromagnetic shielding film.

[0012] Preferably, in step (1), the power of O2 plasma is 50-200 W, and the surface modification treatment time is 10-500 s.

[0013] Preferably, in step (2), the uniaxial pre-stretching is performed to a strain of 0%-150% but not including 0%.

[0014] Preferably, in step (2), the length of the silver nanowires is 10-100 μm and the diameter is 30-100 nm; the solvent used in the silver nanowire dispersion is a mixed solution of water and ethanol, and the volume ratio of water to ethanol is (1-9): (1-9); the concentration of the silver nanowire dispersion is 0.1-2 mg / mL; every 20 cm 2 The elastic transparent substrate is sprayed with 1-6 mL of silver nanowire dispersion.

[0015] Preferably, in step (2), the spraying is performed by using an automatic airbrush with a pressure of 0.1-1 MPa, and the distance between the airbrush and the elastic transparent base layer is 3-20 cm.

[0016] Preferably, in step (3), the soaking time is 1-10 min.

[0017] Preferably, in step (3), the rate of slowly releasing the pre-stretching strain is controlled at 5-50 mm / min.

[0018] Preferably, in step (3), the annealing temperature is 150-200 o C, annealing time is 1-5 h.

[0019] The technical principle of the present invention is as follows: by changing the release environment in the pre-stretching-releasing strain method, that is, by covering with water for immersion and blowing off the residual moisture, a silver nanowire conductive network is constructed in a moist environment. Since the moist moisture acts as a lubricant between the silver nanowires and the elastic substrate layer, during the slow release of the pre-strain, the randomly arranged silver nanowires undergo torsional slippage perpendicular to the pre-strain direction as the elastic substrate layer deforms, thereby transforming the random silver nanowire conductive network into a fence-like structural orientation arrangement perpendicular to the pre-stretching direction, and finally forming a silver nanowire conductive network arranged in a fence-like orientation on the surface of the elastic substrate layer.

[0020] Beneficial effects:

[0021] 1. Compared with the traditional method of releasing pre-strain in the air, which causes the silver nanowires to break and destroy the conductive network, the conductive network formed by the present invention is complete in structure and there is no silver nanowire breakage phenomenon; compared with the wavy structure conductive network formed by releasing pre-strain in solvent water reported in the literature (Adv. Funct. Mater. 2020, 30, 1910214), the present invention maintains the structural rigidity of the silver nanowires themselves, and forms a silver nanowire conductive network with a fence-like structure orientation arrangement, which is beneficial to the photoelectric properties of the transparent film, and at the same time ensures the stable conductivity and electromagnetic shielding performance of the conductive network under large deformation (100% tensile strain);

[0022] 2. The fence-like stretchable transparent electromagnetic shielding film prepared by the present invention has low surface resistance (<10 Ω / sq), high transparency (>70%), and high electromagnetic shielding performance (X full band>30 dB). At the same time, it maintains stable conductivity and electromagnetic shielding performance under 100% tensile strain, and has broad application prospects in the field of stretchable transparent electromagnetic shielding films. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The SEM morphology images of the samples prepared in Comparative Example 1 and Examples 1-3 are shown.

[0024] Figure 2 The optical / electrical properties of the samples prepared in Comparative Example 1 and Examples 1-6.

[0025] Figure 3 The electromagnetic shielding performance of the samples prepared in Comparative Example 1 and Examples 1-6.

[0026] Figure 4 The resistance change rate (R / R0) of the samples prepared in Comparative Example 1 and Examples 1-3 under different tensile strains.

[0027] Figure 5 It is the electromagnetic shielding effectiveness change rate (SE / SE0) of the samples prepared in Comparative Example 1 and Examples 1-3 under different tensile strains.

[0028] Figure 6 The changes in surface resistance and electromagnetic shielding performance of the samples prepared in Example 2 and Comparative Example 2, i.e., the transparent electromagnetic shielding films, before and after annealing. DETAILED DESCRIPTION

[0029] To make the present invention clearer and more specific, the present invention is further described in detail below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0030] Example 1

[0031] A fence-like structure stretchable transparent electromagnetic shielding film, comprising the following steps:

[0032] (1) Use O2 plasma to modify the surface of the PDMS substrate in a vacuum environment. The plasma treatment conditions are: power 100 W, treatment time 90 s;

[0033] (2) Place the PDMS substrate (4 × 5 cm) that has been surface-modified in step (1) 2 ) was pre-stretched uniaxially along its length to 50% strain, and then 6 mL of silver nanowire dispersion (concentration of 1 mg / mL, solvent was a mixture of water and anhydrous ethanol in a volume ratio of 5:5, the length of the silver nanowire was 50 μm, and the diameter was 30 nm) was sprayed on its surface using an automatic spray brush to form a silver nanowire transparent conductive network; the spray brush air pressure was 0.5 MPa, and the distance between the spray brush and the PDMS substrate layer was 5 cm;

[0034] (3) The surface of the silver nanowire conductive network formed in step (2) was evenly and completely covered with a layer of water. After soaking for 3 min, the residual water on the surface was blown away, and then the pre-stretching strain was released at a speed of 10 mm / min to a completely relaxed state. Finally, the pre-stretching strain was heated at 190 °C. oC for 2 h to obtain a stretchable transparent electromagnetic shielding film with a fence-like structure, in which the surface density of the silver nanowire transparent conductive network layer is 0.30 mg / cm 2 .

[0035] Example 2

[0036] The difference from Example 1 is that in step (2), uniaxial pre-stretching is performed until 100% strain occurs; the rest is the same as Example 1.

[0037] In the fence-like stretchable transparent electromagnetic shielding film prepared in this embodiment, the surface density of the silver nanowire transparent conductive network layer is the same as that in Example 1, which is also 0.30 mg / cm 2 .

[0038] Example 3

[0039] The difference from Example 1 is that in step (2), uniaxial pre-stretching is performed until a strain of 150% occurs; the rest is the same as Example 1.

[0040] In the fence-like stretchable transparent electromagnetic shielding film prepared in this embodiment, the surface density of the silver nanowire transparent conductive network layer is the same as that in Example 1, which is also 0.30 mg / cm 2 .

[0041] Example 4

[0042] The difference from Example 1 is that in step (2), the volume of the air-sprayed silver nanowire dispersion is 3 mL during uniaxial pre-stretching to produce 100% strain; the rest is the same as Example 1.

[0043] In the fence-like stretchable transparent electromagnetic shielding film prepared in this embodiment, the surface density of the silver nanowire transparent conductive network layer is 0.15 mg / cm 2 .

[0044] Example 5

[0045] The difference from Example 1 is that in step (2), the uniaxial pre-stretching is performed to produce 100% strain and the volume of the air-sprayed silver nanowire dispersion is 4 mL; the rest is the same as Example 1.

[0046] In the fence-like stretchable transparent electromagnetic shielding film prepared in this embodiment, the surface density of the silver nanowire transparent conductive network layer is 0.20 mg / cm 2 .

[0047] Example 6

[0048] The difference from Example 1 is that in step (2), the uniaxial pre-stretching is performed to produce 100% strain and the volume of the air-sprayed silver nanowire dispersion is 5 mL; the rest is the same as Example 1.

[0049] In the fence-like stretchable transparent electromagnetic shielding film prepared in this embodiment, the surface density of the silver nanowire transparent conductive network layer is 0.25 mg / cm 2 .

[0050] Comparative Example 1

[0051] The difference from Example 1 is that in step (2), uniaxial pre-stretching is performed to 0% strain (i.e., no pre-stretching); the rest is the same as Example 1.

[0052] Comparative Example 2

[0053] The difference from Example 2 is that in step (3), the annealing treatment is omitted; the rest is the same as Example 2.

[0054] A scanning electron microscope was used to characterize the morphology of the silver nanowire conductive network on the surface of the transparent electromagnetic shielding film; an ultraviolet-visible absorption spectrometer was used to characterize the transparency of the transparent electromagnetic shielding film; a four-probe instrument tester was used to characterize the surface resistance of the transparent electromagnetic shielding film; a vector network analyzer was used to characterize the electromagnetic shielding performance of the transparent electromagnetic shielding film.

[0055] Figure 1 The SEM morphology images of the samples prepared in Comparative Example 1 and Examples 1-3, 0% corresponds to the sample prepared in Comparative Example 1, 50%, 100% and 150% correspond to the samples prepared in Examples 1-3 respectively. Figure 1 It can be seen that: for the sample prepared without pre-stretching (the sample prepared in Comparative Example 1), the surface silver nanowire conductive network presents a disordered arrangement. In comparison, for the sample prepared by pre-stretching (the samples prepared in Examples 1-3), the surface silver nanowire conductive network presents a fence-like structure orientation distribution perpendicular to the pre-stretching direction. As the pre-stretching strain increases from 50% to 150%, the orientation degree of the silver nanowires presents a gradually increasing trend.

[0056] Figure 2 The optical / electrical properties of the samples prepared in Comparative Example 1 and Examples 1-6 are shown in Table 1. Figure 2It can be seen from ab that the transparent conductive films prepared with pre-stretching strains of 0%, 50%, 100% and 150% (corresponding to the samples prepared in Example 1, Examples 1, 2 and 3) have a transmittance of about 70% in the visible light band; as the pre-stretching strain increases, the surface resistance of the corresponding transparent conductive film increases from 6.03Ω / sq to 11.13Ω / sq; in comparison, the photoelectric properties of the 100% pre-stretching strain sample are close to those of the non-pre-stretching sample, so the photoelectric properties of the different conductive network densities on the surface of the pre-stretching 100% strain sample are studied, such as Figure 2 As shown in cd, as the conductive network density increases from 0.15 to 0.30 mg / cm 2 (Samples prepared in Examples 2, 4, 5, and 6), the light transmittance of the film decreased from 83.2% to 73.7%, and the surface resistance decreased from 51.76 Ω / sq to 7.68 Ω / sq. Among them, the pre-stretching strain was 100%, the surface density was 0.30 mg / cm 2 The film sample (prepared in Example 2) has a transmittance of 73.7% and a surface resistance of 7.68 Ω / sq, which basically meets the requirements of transparent electromagnetic shielding films.

[0057] Figure 3 The electromagnetic shielding performance of the samples prepared in Comparative Example 1 and Examples 1-6. Figure 3 As shown in a, the transparent conductive films prepared with different pre-stretching strains (corresponding to the samples prepared in Example 1, Examples 1, 2, and 3) have an electromagnetic shielding performance of more than 30 dB in the X-band, which means that when electromagnetic waves pass through the film, more than 99.9% of the electromagnetic wave energy will be shielded. Figure 3 As shown in Fig. 2b, the electromagnetic shielding performance of the samples with 100% pre-stretching strain (samples prepared in Examples 2, 4, 5, and 6) gradually increases with the increase of surface conductive network density, from 18.8 dB to 32.2 dB. 2 The film sample (prepared in Example 2) has a light transmittance of 73.7% and a shielding effectiveness of 32.2 dB, which basically meets the requirements of transparent electromagnetic shielding films.

[0058] Figure 4 The resistance change rate (R / R0) of the samples prepared in Comparative Example 1 and Examples 1-3 under different tensile strains. Figure 4As shown, the surface conductive network of the non-pre-stretched sample (Comparative Example 1) is destroyed under tensile strain conditions, and the resistance change rate (R / R0) is more than 8 under only 20% tensile strain, and the surface resistance change rate exceeds the test range (much greater than 20) under 40% to 100% tensile strain; the sample prepared by 50% pre-stretching (Example 1) has a maximum surface resistance change rate of more than 13 as the tensile strain increases; in comparison, the samples prepared by 100% and 150% pre-stretching (Examples 2 and 3) still maintain a complete conductive network under tensile conditions due to the twisting deformation of the simulated fence structure orientation without changing the network crosslinking density. Therefore, under a tensile strain within 100%, the surface resistance change rate is less than 1.5, indicating that the sample can still maintain stable conductivity under large deformation conditions and has stretchable conductive properties.

[0059] Figure 5 The electromagnetic shielding effectiveness change rate (SE / SE0) of the samples prepared in Comparative Example 1 and Examples 1-3 under different tensile strains. Figure 5 As shown, since the conductivity of the non-pre-stretched sample (Comparative Example 1) drops sharply under the stretching state, its electromagnetic shielding performance also drops significantly with the increase of the tensile strain. When the tensile strain exceeds 80%, the electromagnetic shielding performance of the film is almost completely reduced. The 50% pre-stretched strain sample (Example 1) can still maintain at least 80% of the original shielding effectiveness under the condition of less than 50% tensile strain. When the tensile strain exceeds 50%, its electromagnetic shielding performance drops sharply. At 100% tensile strain, only about 10% of the shielding effectiveness of the original film is maintained. In comparison, the samples prepared by 100% and 150% pre-stretching (Examples 2 and 3) still retain about 80% of the shielding effectiveness of the original film at 100% tensile strain because the conductive network is well maintained during the stretching process, indicating that the sample has good stretchable electromagnetic shielding performance.

[0060] Figure 6 From the changes in surface resistance and electromagnetic shielding performance of the samples prepared in Example 2 and Comparative Example 2, i.e., the transparent electromagnetic shielding films, before and after annealing, it can be found that: through the high-temperature annealing treatment, welding occurs at the overlap of the surface silver nanowire conductive network, resulting in a decrease in the contact resistance of the conductive network at the overlap, thereby improving the conductivity and electromagnetic shielding performance of the transparent electromagnetic shielding films to a certain extent.

[0061] In summary, the fence-like structured oriented silver nanowire conductive network constructed by the present invention can be twisted and deformed without destroying the integrity of the conductive network, so that the conductive network has stretchable properties and maintains stable conductivity and electromagnetic shielding effectiveness under large strain conditions lower than its pre-stretching strain. A comprehensive comparison of the conductivity, electromagnetic shielding performance and stretchability of the samples shows that after 100% pre-stretching strain and a surface density of 0.30 mg / cm 2The transparent electromagnetic shielding film has the best comprehensive performance. Therefore, the present invention obtains a novel transparent electromagnetic shielding film with a silver nanowire conductive network with a fence-like oriented structure through a novel and simple pre-strain release environment change, and obtains a 32.2 dB shielding performance at a transmittance of 73.7%. Under a large tensile strain of 100%, the resistance change rate (R / R0) is less than 1.5, and the electromagnetic shielding effectiveness maintains 80% of the original shielding effectiveness.

Claims

1. A method for preparing a stretchable transparent electromagnetic shielding film with a fence-like structure, characterized in that: The fence-like stretchable transparent electromagnetic shielding film comprises an elastic transparent base layer and a surface layer deposited thereon, wherein the elastic transparent base layer is a polydimethylsiloxane film or a thermoplastic polyurethane film, and the surface layer is a silver nanowire conductive network layer, and the silver nanowires are distributed on the elastic transparent base layer in a fence-like structure orientation; The preparation steps are as follows: (1) Using O2 plasma to perform surface modification on the elastic transparent substrate in a vacuum environment; (2) uniaxially pre-stretching the elastic transparent substrate layer subjected to surface modification treatment in step (1) until strain occurs, and spraying a silver nanowire dispersion on the surface of the elastic transparent substrate layer to form a silver nanowire transparent conductive network; (3) The surface of the silver nanowire conductive network formed in step (2) is uniformly covered with a layer of water. After soaking, the residual water on the surface is blown away, and the pre-stretching strain is slowly released to a completely relaxed state, and annealing is performed to obtain a fence-like structure stretchable transparent electromagnetic shielding film, wherein the fence-like structure is a fence-like orientation distribution of silver nanowires perpendicular to the pre-stretching direction on the elastic transparent substrate layer.

2. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (1), the power of O2 plasma is 50-200 W, and the surface modification treatment time is 10-500 s.

3. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (2), the uniaxial pre-stretching is performed to a strain of 0%-150% but not including 0%.

4. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (2), the length of the silver nanowire is 10-100 μm and the diameter is 30-100 nm; the solvent used in the silver nanowire dispersion is a mixed solution of water and ethanol, and the volume ratio of water to ethanol is (1-9): (1-9); the concentration of the silver nanowire dispersion is 0.1-2 mg / mL; every 20 cm 2 The elastic transparent substrate is sprayed with 1-6 mL of silver nanowire dispersion.

5. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (2), the spraying is carried out by using an automatic airbrush with a pressure of 0.1-1 MPa, and the distance between the airbrush and the elastic transparent base layer is 3-20 cm.

6. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (3), the soaking time is 1-10 min.

7. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (3), the rate of slowly releasing the pre-stretching strain is controlled at 5-50 mm / min.

8. The method for preparing the fence-like structure stretchable transparent electromagnetic shielding film according to claim 1, characterized in that: In step (3), the annealing temperature is 150-200 o C, annealing time is 1-5 h.

9. A stretchable transparent electromagnetic shielding film with a fence-like structure prepared by the preparation method according to any one of claims 1 to 8.

Citation Information

Patent Citations

  • Flexible conductive film, producing method thereof, and display panel

    US20220016874A1